Methane emissions from municipal landfills: a case study of Chandigarh and economic evaluation for waste-to-energy generation in India - Mor, Suman; Kaur, Kamalpreet; Ravindra, Khaiwal (Frontiers in Sustainable Cities, 2024)
The present study highlights the dual benefits of landfill gas utilization: mitigating greenhouse gas emissions and generating renewable energy. Municipal waste, containing a large proportion of organic matter, is dumped into Solid Waste Disposal Sites (SWDS), which, after anaerobic decomposition, releases methane (CH4). This study aims to assess the methane emissions from the SWDS of Chandigarh, India, and evaluate the potential for electricity generation from captured landfill gas. Waste samples were obtained using the quartile method and examined for proximate and ultimate analysis. The inventory and estimation of CH4 generation were done using the International Panel on Climate Change (IPCC) methodology, including the potential of electricity generation from the CH4 generated. It has been observed that Chandigarh generates around 350 tons per day (TPD) of waste, with organic material constituting over 50% on average. The estimated amount of municipal waste with observed composition led to the generation of 0.34 Gg/yr of CH4. Depending on the efficiency of the gas energy system, 0.27 MW to 0.77 MW of electric power can be produced in Chandigarh. The study also provides a broader context for solid waste management in India. Analysis of national data revealed that India generates about 160,038.9 TPD of solid waste, with only about half (79,956.3 TPD) being treated. The country has 3,184 existing dumpsites, with significant variations across states. As per the present analysis, when extrapolated to a national scale, India could potentially generate 5,167 MW to 14,355 MW of power from all its SWDS, resulting in annual financial gains of 4.7 to 13 billion USD. These findings underscore the importance of implementing integrated waste management strategies that prioritize waste reduction, efficient treatment, and energy recovery from landfill gas.